A Social Emergency Tasks in Emergency Response Centers (ERCÂ´s) of Finland - Anne Mäkinen (Social Work and Society)
In Finland, the Emergency Response Center (ERC) is responsible for the pan-European 112 emergency number service. The service is produced by tax revenues and the call to the emergency number is free of charge all to the citizen. There are six ERC´s in Finland with their own areas and each year they receive more than 3 million emergency calls. Calls include, in addition to emergency treatment, rescue service and police tasks, but also tasks which relating to social emergencies. This article opens the perspective of the general characteristics of the social emergencies of Finnish modern society through the ERC`s. The study examined how many social tasks were created in the ERC´s during the years 2011 - 2015 and what was the quality of those tasks. The material was collected in tabular format and was analyzed by simplest methods for the percentage and frequency distribution. The main customer groups of the social tasks in the ERC´s were the children and young people, as well as the elderly, and the tasks were mainly related to the review of the urgent nurture and care. The number of social tasks seemed to grow yearly. The role of the ERC´s as a recipient of social emergencies in Finnish society was considered a phenomenon. They have been given a permanent foothold as the first receiving authority for urgent social tasks, assistance and security and serving the first authority link via the 112-emergency number.